2015
DOI: 10.1007/s00382-015-2879-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land-surface initialization on sub-seasonal to seasonal forecasts over Europe

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 79 publications
3
65
0
Order By: Relevance
“…For instance, realistic initialization of snow enhances the forecast skill on S2S time scales (Schlosser and Mocko, 2003;Peings et al, 2011;Jeong et al, 2012;Orsolini et al, 2013;Lin et al, 2016). Similar results have been obtained by initializing soil moisture (Dirmeyer, 2000;Douville, 2003;Conil et al, 2009;Koster et al, 2010;Koster et al, 2011;van den Hurk et al, 2012;Kumar et al, 2014), as well as both snow and soil moisture (Douville, 2010;Prodhomme et al, 2016;Thomas et al, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…For instance, realistic initialization of snow enhances the forecast skill on S2S time scales (Schlosser and Mocko, 2003;Peings et al, 2011;Jeong et al, 2012;Orsolini et al, 2013;Lin et al, 2016). Similar results have been obtained by initializing soil moisture (Dirmeyer, 2000;Douville, 2003;Conil et al, 2009;Koster et al, 2010;Koster et al, 2011;van den Hurk et al, 2012;Kumar et al, 2014), as well as both snow and soil moisture (Douville, 2010;Prodhomme et al, 2016;Thomas et al, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…Although it is beyond the scope of this work to analyse in depth the factors explaining this relative success, previous seasonal studies showed the influence of anomalous initial conditions in subsequent summer heat waves. For example, sea surface temperature warm anomalies in June 2003 likely contributed to enhance the severity of the following summer heat wave (Feudale and Shukla, 2011a, b) and low soil moisture in spring was revealed as a key ingredient of the 2010 heat wave over Russia (Prodhomme et al, 2016). In 2015, the sea surface temperature of the Mediterranean and Near-Atlantic was not particularly warm in early June, whereas soils were anomalously dry over Western Europe (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A larger re-forecast period would allow a better sampling. Additionally, it would allow us to perform a conditional skill study by selecting enough start dates with strong external forcing in the initial conditions, since these may lead to enhanced predictability of a particular extreme event such as in July 2015 (Prodhomme et al, 2016). This point is further discussed in Sect.…”
Section: Re-forecast Forecastmentioning
confidence: 99%
“…Prodhomme et al, 2016a), the improvement of initialization procedures (e.g. Prodhomme et al, 2016b), and the more accurate representation of some physical processes (e.g. Hourdin et al, 2013) has considerably advanced the ac-curacy of W&C services, with current state-of-the-art products showing good forecast skills even over seasonal and longer timescales (Doblas-Reyes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%